CLASSIC SKELETAL PROSTHESIS - A VIABLE CLINICAL TECHNOLOGICAL APPROACH - Irina Gradinaru; Georgiana Macovei; Loredana Liliana Hurjui; Claudia Cristina Tarniceriu; Mihaela Mitrea; Carina Balcos; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2022)
The design of skeletal partial removable dentures must be made following a thorough analysis of their possibilities of movement during the exercise of the functions of the dental-maxillary apparatus. Through the study we aim to individualize the balance between aesthetics and functionality within the clinical-technological algorithm for making partially mobilizable skeletal prostheses, anchored in the classic register, therapeutic solutions dictated by the particularity of the clinical case. The algorithm for the realization of a number of 36 removable skeletal prostheses anchored in the classic register made of Cr-Co alloys, respectively Ni-Cr, was evaluated, their final design being grafted on the specificity of the clinical-biological indices corroborated with the therapeutic principles for each clinical case. The classical systems of therapeutic solution of partially extended edentation are valid in any conditions of local, loco-regional pathology, subsequent to the resolution of the complications present at the level of the muco-osseous or dental-periodontal support.